Catalytic cracking catalyst with hierarchical pore structure as well as preparation method and application of catalytic cracking catalyst

By introducing a multi-stage pore structure into the catalyst, using the step pore distribution of large-particle aluminum oxide, modified concave and convex rod soil and mesoporous materials, the problem of low diffusion and reaction efficiency of the catalyst on macromolecules is solved, and low coke is achieved Improved productivity and high-value product selectivity.

CN119236997APending Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310805165.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When existing catalytic cracking catalysts treat heavy raw oil, it is difficult to effectively diffuse and deposit macromolecules, resulting in high coke yield, low active center utilization, and insufficient selectivity for high-value products.

Method used

Using catalysts with multi-stage pore structures, including large-particle alumina, modified concave and convex rod soil and mesoporous materials, optimize the diffusion and reaction of macromolecules through the distribution of step pore structures, combine suitable binders and clays to form rich pore structure to improve catalytic activity.

Benefits of technology

It significantly reduces the coke yield, improves the selectivity of low-carbon olefins and gasoline, enhances the catalyst's wear resistance and heavy oil cracking ability, and improves the total liquid yield of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236997A_ABST
    Figure CN119236997A_ABST
Patent Text Reader

Abstract

The invention relates to a catalytic cracking catalyst with a hierarchical pore structure and a preparation method and application thereof.The catalytic cracking catalyst comprises, on the basis of the total weight of the catalytic cracking catalyst, 5-30 wt% of large-particle-size aluminum oxide, 5-40 wt% of a mesoporous material, 5-35 wt% of modified attapulgite and 20-50 wt% of a molecular sieve, 2 to 35% by weight of a binder and 0 to 20% by weight of clay; the number of particles with the average particle size of 5-30 nm in the large-particle-size aluminum oxide accounts for 80% or above of the total number of particles; the total pore volume of the catalytic cracking catalyst is 0.25 mL / g or more, the pore volume of 4-6nm pores accounts for 10-35% of the total pore volume, the pore volume of 6-20nm pores accounts for 30-60% of the total pore volume, and the pore volume of 20-100nm pores accounts for 10-30% of the total pore volume. The catalytic cracking catalyst disclosed by the invention has the advantages of good anti-wear index, low coke yield and high selectivity of low-carbon olefin and gasoline.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a catalytic cracking catalyst with a multi-level pore structure and a preparation method and application thereof. Background Art

[0002] Pore ​​structure is one of the important characteristics of catalytic cracking catalysts. It is a channel for hydrocarbon molecules to diffuse and transfer and an important place for catalytic reactions. With the heavy and inferior quality of catalytic cracking feedstock, the feedstock contains a large amount of heavy metals (Fe, Ni and V, etc.) and has a high carbon residue value. These heavy metals and carbon residues mainly come from macromolecules such as colloids and asphaltene. The molecular size of these macromolecules is relatively large (about 2.5-15nm), which makes it difficult to enter the molecular sieve pores of the catalyst, often blocking the molecular sieve pores and depositing near the pores, resulting in catalyst deactivation, increased coke yield, and reduced molecular sieve utilization.

[0003] Therefore, in order to maximize the cracking capacity of heavy crude oil while reducing the coke yield, the catalyst is required to have a rich pore distribution that can improve the mass transfer, diffusion and reaction of macromolecular reactants. In addition to requiring the catalytic cracking catalyst to have a rich microporous structure, it is also required to have a gradient-distributed mesoporous and macroporous structure. The macropores are conducive to improving the diffusion of macromolecules such as metal-containing asphaltene, and promoting the rapid diffusion and deposition of impurity-containing macromolecules into the internal pores of the catalyst, while the mesopores can provide the largest possible specific surface for the reaction, promote the removal and deposition of impurities, thereby improving the catalyst's ability to resist heavy metal pollution, reducing coke formation, and improving the accessibility of active centers.

[0004] CN105688977A discloses a method for preparing a catalytic cracking catalyst containing pseudo-boehmite. The method comprises mixing and stirring part of the pseudo-boehmite with a silicon-containing solution for more than 15 minutes to prepare a modified pseudo-boehmite A, mixing and slurrying the modified pseudo-boehmite A, the remaining pseudo-boehmite B, and clay to prepare a matrix slurry containing pseudo-boehmite, mixing the matrix slurry and the molecular sieve slurry, homogenizing, forming and drying, and ion exchange to obtain a catalytic cracking catalyst. The catalyst prepared by the method has a good anti-wear index, a high macropore volume, a strong heavy oil conversion ability, and a good coke selectivity, but when the catalyst is used in the catalytic cracking reaction process of crude oil, the selectivity for high-value products, especially low-carbon olefins and gasoline needs to be improved. Summary of the invention

[0005] The purpose of the present disclosure is to provide a catalytic cracking catalyst with a multi-level pore structure, a preparation method and an application thereof, wherein the catalytic cracking catalyst has a good anti-wear index, a low coke yield, and a high selectivity for light olefins and gasoline.

[0006] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a catalytic cracking catalyst having a multi-level pore structure. Based on the total weight of the catalytic cracking catalyst, the catalytic cracking catalyst contains 5-30 wt% of large-particle alumina, 5-40 wt% of mesoporous material, 5-35 wt% of modified attapulgite, 20-50 wt% of molecular sieve, 2-35 wt% of binder and 0-20 wt% of clay; the number of particles with an average particle size of 5-30 nm in the large-particle alumina accounts for more than 80% of the total number of particles; the mesoporous material contains silicon and / or aluminum;

[0007] The total pore volume of the catalytic cracking catalyst is above 0.25 mL / g, the pore volume of 4-6 nm pores accounts for 10-35% of the total pore volume, the pore volume of 6-20 nm pores accounts for 30-60% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 10-30% of the total pore volume.

[0008] Optionally, the catalytic cracking catalyst contains 10-30 wt% of large particle size alumina, 10-35 wt% of mesoporous material, 10-35 wt% of modified attapulgite, 25-45 wt% of molecular sieve, 5-30 wt% of binder and 0-15 wt% of clay.

[0009] Optionally, the total pore volume of the catalytic cracking catalyst is 0.3-0.5 mL / g, the pore volume of the 4-6 nm pores accounts for 15-35% of the total pore volume, the pore volume of the 6-20 nm pores accounts for 30-55% of the total pore volume, and the pore volume of the 20-100 nm pores accounts for 15-30% of the total pore volume.

[0010] Optionally, the number of particles with an average particle size of 5-30 nm in the large-particle alumina accounts for 85-95% of the total number of particles; the large-particle alumina is selected from one or more of large-particle pseudo-boehmite, large-particle boehmite and large-particle aluminum sol, preferably large-particle pseudo-boehmite;

[0011] The total pore volume of the mesoporous material is 0.8-2.5 mL / g, the pore volume of 6-20 nm pores accounts for more than 80% of the total pore volume, preferably 85-95%, and the specific surface area is 200-400 m 2 / g, preferably 220-400m 2 / g; the mesoporous material is selected from one or more of conventional pseudo-boehmite, alumina, silica and alumina-silica, preferably conventional pseudo-boehmite and / or alumina;

[0012] The total pore volume of the modified attapulgite is 0.3 mL / g or more, preferably 0.3-0.5 mL / g, the pore volume of 10-100 nm pores accounts for more than 80% of the total pore volume, preferably 85-95%, and the specific surface area is 100 m 2 / g or more, preferably 100-300m 2 / g;

[0013] The molecular sieve is selected from NaY type molecular sieve, and the NaY type molecular sieve is one or more of the modified high silicon-aluminum ratio Y zeolite, MFI type zeolite and Beta zeolite;

[0014] The binder is selected from one or more of aluminum sol, silica sol, silica-alumina sol, acidified pseudo-boehmite, aluminum phosphate sol and zirconium sol, preferably aluminum sol and / or silica sol;

[0015] The clay is selected from one or more of kaolin, bentonite, montmorillonite, sepiolite, diatomaceous earth and rectorite, preferably kaolin.

[0016] The second aspect of the present disclosure provides a method for preparing the catalytic cracking catalyst having a multi-level pore structure according to the first aspect of the present disclosure, the method comprising:

[0017] S1, mixing attapulgite and a first solvent, controlling the pH value of the obtained first mixture to be 1.5-4.5, stirring at 20-90° C. for 30-120 min, and taking out a solid to obtain modified attapulgite;

[0018] S2, mixing the modified attapulgite, mesoporous material, clay, molecular sieve, large-size alumina, binder and a second solvent, controlling the pH value of the obtained second mixture to be 2.5-4.5, and then drying and calcining.

[0019] Optionally, step S1 comprises: mixing the attapulgite and the first solvent in a weight ratio of 1:(5-20), and adjusting the pH value of the first mixture to 1.5-4.0 using an acid solution;

[0020] The acid solution contains organic acid and / or inorganic acid; the organic acid is selected from one or more of oxalic acid, acetic acid and citric acid, and the inorganic acid is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, ammonium sulfate and ammonium chloride.

[0021] Optionally, step S2 includes:

[0022] SS1, mixing the modified attapulgite, the mesoporous material, the clay, the binder and the second solvent to obtain a third mixture with a solid content of 10-50 wt %;

[0023] SS2, mixing the third mixture, the molecular sieve and the large-particle alumina to obtain a second mixture with a solid content of 10-50 wt %, and drying and calcining the obtained second mixture; or,

[0024] SS2. Mix the molecular sieve, the large-particle alumina and the third solvent and control the pH value of the mixture to be 2.5-4.5 to obtain a fourth mixture with a solid content of 10 to 50 weight %; mix the fourth mixture with the third mixture to obtain the second mixture, and dry and calcine the obtained second mixture.

[0025] Optionally, the drying conditions include: a temperature of 80-180°C;

[0026] The calcination conditions include: a temperature of 400-600° C. and a time of 0.5-5.0 hours.

[0027] A third aspect of the present disclosure provides an application of the catalytic cracking catalyst with a multi-level pore structure provided by the first aspect of the present disclosure in the catalytic cracking of crude oil.

[0028] Optionally, the catalytic cracking conditions include: temperature of 450-560° C., time of 1-3 s, and catalyst-oil mass ratio of 3-10.

[0029] Through the above technical scheme, the catalytic cracking catalyst disclosed in the present invention has a good anti-wear index, low coke yield, excellent selectivity for high-value products, especially high selectivity for low-carbon olefins and gasoline. Its multi-level medium and large pore structure has the following advantages: the 20-100nm medium and large pore structure is conducive to improving the diffusion efficiency of macromolecules such as crude oil polycyclic aromatics, inhibiting condensation and coking, and the 6-20nm pore structure is the main place for pre-cracking of crude oil macromolecules, promoting the efficient conversion of macromolecules to medium molecules; the 2-6nm pore structure further promotes the generation of medium-small molecules, allowing them to more effectively enter the micropores of different types of molecular sieves. At the same time, the multi-level pore distribution is also conducive to the efficient desorption of molecules of different product sizes from the catalyst pores, improving product selectivity.

[0030] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0032] Figure 1 This is a pore size distribution diagram of the catalytic cracking catalyst prepared in Example 1 of the present disclosure.

[0033] Figure 2 This is the pore size distribution diagram of the modified attapulgite used in Example 1 of the present disclosure.

[0034] Figure 3 It is the pore size distribution diagram of the catalytic cracking catalyst prepared in Comparative Example 1 of the present disclosure. DETAILED DESCRIPTION

[0035] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0036] The first aspect of the present disclosure provides a catalytic cracking catalyst having a multi-level pore structure. Based on the total weight of the catalytic cracking catalyst, the catalytic cracking catalyst contains 5-30 wt% of large-particle alumina, 5-40 wt% of mesoporous material, 5-35 wt% of modified attapulgite, 20-50 wt% of molecular sieve, 2-35 wt% of binder and 0-20 wt% of clay; the number of particles with an average particle size of 5-30 nm in the large-particle alumina accounts for more than 80% of the total number of particles; the mesoporous material contains silicon and / or aluminum;

[0037] The total pore volume of the catalytic cracking catalyst is above 0.25 mL / g, the pore volume of 4-6 nm pores accounts for 10-35% of the total pore volume, the pore volume of 6-20 nm pores accounts for 30-60% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 10-30% of the total pore volume.

[0038] The catalyst disclosed in the present invention has a multi-level meso- and macro-pore structure, wherein the 4-6 nm mesopores mainly come from the pores formed by the accumulation of large-size alumina particles, the 6-20 nm mesopores mainly come from the mesoporous material, and the 20-100 nm meso- and macro-pores mainly come from modified attapulgite. The stepped pore structure formed by the compounding of the above three specific materials is beneficial to the diffusion and pre-cracking of molecules of different sizes in the catalytic cracking feedstock oil, which is beneficial to reducing the formation of coke and improving the selectivity for high-value products, especially the selectivity for low-carbon olefins and gasoline. When used in catalytic cracking treatment, it has a higher heavy oil cracking capacity and a total liquid yield.

[0039] The range values ​​​​expressing sizes in the present disclosure all include the endpoint values ​​at both ends. For example, in "the pore volume of 4-6nm pores accounts for 10-35% of the total pore volume", 4-6nm pores refer to pores with a pore diameter ranging from 4nm to 6nm; for another example, in "the pore volume of 6-20nm pores accounts for 30-60% of the total pore volume", 6-20nm pores refer to pores with a pore diameter ranging from 6nm to 20nm.

[0040] In the present disclosure, the number of particles with an average particle size of 5-30nm and the total number of particles in large-particle alumina are analyzed using a JEM-2000FX-II transmission electron microscope from a Japanese electronics company. The average particle size is obtained by randomly measuring more than 10 grain projections in the TEM image of the sample and taking the average value of their maximum circumscribed circle diameters.

[0041] In a specific embodiment of the present disclosure, the catalytic cracking catalyst contains 10-30 wt% of large particle size alumina, 10-35 wt% of mesoporous material, 10-35 wt% of modified attapulgite, 25-45 wt% of molecular sieve, 5-30 wt% of binder and 0-15 wt% of clay.

[0042] In a specific embodiment of the present disclosure, the total pore volume of the catalytic cracking catalyst is 0.3-0.5 mL / g, preferably 0.30-0.45, the pore volume of the 4-6 nm pores accounts for 15-35% of the total pore volume, preferably 15-30%, the pore volume of the 6-20 nm pores accounts for 30-55% of the total pore volume, preferably 30-50%, and the pore volume of the 20-100 nm pores accounts for 15-30% of the total pore volume, preferably 15-25%.

[0043] In a specific embodiment of the present disclosure, the number of particles with an average particle size of 5-30 nm in the large-particle alumina accounts for 85-95% of the total number of particles; the large-particle alumina is selected from one or more of large-particle pseudo-boehmite, large-particle boehmite and large-particle aluminum sol, preferably large-particle pseudo-boehmite.

[0044] In a specific embodiment of the present disclosure, the total pore volume of the mesoporous material is 0.8-2.5 mL / g, preferably 1.0-2.2 mL / g, the pore volume of 6-20 nm pores accounts for more than 80% of the total pore volume, preferably 85-95%, and the specific surface area is 200-400 m 2 / g, preferably 220-400m 2 / g; the mesoporous material is selected from one or more of conventional pseudo-boehmite, alumina, silica and alumina-silica, preferably conventional pseudo-boehmite and / or alumina.

[0045] In a specific embodiment of the present disclosure, the total pore volume of the modified attapulgite is 0.3 mL / g or more, preferably 0.3-0.5 mL / g, the pore volume of 10-100 nm pores accounts for more than 80% of the total pore volume, preferably 85-95%, and the specific surface area is 100 m 2 / g or more, preferably 100-300m 2 / g. In the present disclosure, the pore parameters and specific surface area of ​​the mesoporous material and the modified attapulgite can be measured by a low-temperature nitrogen adsorption method, which is well known to those skilled in the art and will not be described in detail here. The modified attapulgite disclosed in the present disclosure has a low content of impurity metals such as Fe and Ca, and has a high specific surface area and pore volume.

[0046] In a specific embodiment of the present disclosure, the molecular sieve is one or more of a Y-type molecular sieve, an MFI-type zeolite and a Beta zeolite, and the Y-type molecular sieve may be a Y zeolite obtained by modifying a NaY-type molecular sieve. The Y zeolite obtained by modifying the NaY-type molecular sieve may include but is not limited to HY, REY, REHY, USY and REUSY.

[0047] In a specific embodiment of the present disclosure, the binder is selected from one or more of aluminum sol, silica sol, silica-alumina sol, acidified pseudo-boehmite, aluminum phosphate sol and zirconium sol, preferably aluminum sol and / or silica sol.

[0048] In a specific embodiment of the present disclosure, the clay is selected from one or more of kaolin, bentonite, montmorillonite, sepiolite, diatomaceous earth and rectorite, preferably kaolin.

[0049] The second aspect of the present disclosure provides a method for preparing the catalytic cracking catalyst with a multi-level pore structure provided by the first aspect of the present disclosure, the method comprising: S1, mixing attapulgite and a first solvent, controlling the pH value of the obtained first mixture to be 1.5-4.5, preferably 1.5-4.0, stirring at 20-90°C for 30-120min, and taking out the solid to obtain modified attapulgite; S2, mixing the modified attapulgite, mesoporous material, clay, molecular sieve, large-particle alumina, binder and second solvent, controlling the pH value of the obtained second mixture to be 2.5-4.5, and then drying and calcining.

[0050] The present disclosure does not impose any specific restrictions on the method of removing the solid, for example, filtration, centrifugal separation, etc. The first solvent, the second solvent and the third solvent in the present disclosure can be independently selected from deionized water and / or decationized water.

[0051] The method disclosed in the present invention can prepare a catalytic cracking catalyst with a multi-level pore structure. The catalyst has a good anti-wear index, a low coke yield, and a high selectivity for light olefins and gasoline. Using the catalyst in the catalytic cracking of crude oil is beneficial to increasing the total liquid yield.

[0052] According to the present disclosure, the large-particle pseudo-boehmite can be selected from commercial products, or can be prepared in the following manner, but is not limited to the following preparation method: (1) a sodium aluminate solution with a concentration of 15-60gAl2O3 / L is neutralized with a carbon dioxide gas with a volume fraction of 40-60% to form a gel, the gelling temperature is not higher than 50°C, and the pH value of the gelling end point is 9-11; (2) the gelled slurry is aged in stages in a closed container, firstly programmed to 50-100°C for aging for 30-120min, preferably programmed to 60-80°C for aging for 40-80min; and then programmed to 100-220°C for aging for 1-10h, preferably programmed to 120-180°C for aging for 2-6h. (3) the aged slurry is filtered and washed with deionized water; and (4) the filter cake obtained after washing is dried to obtain large-particle pseudo-boehmite.

[0053] In a specific embodiment of the present disclosure, step S1 comprises: after mixing the attapulgite and the first solvent in a weight ratio of 1:(5-20), adjusting the pH value of the first mixture to 1.5-4.0 with an acid solution, preferably, drying the obtained modified attapulgite. In the present disclosure, the acid solution is well known to those skilled in the art, and the acid solution may contain an organic acid and / or an inorganic acid; the organic acid may be selected from one or more of oxalic acid, acetic acid and citric acid, and the inorganic acid may be selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, ammonium sulfate and ammonium chloride.

[0054] In a specific embodiment of the present disclosure, step S2 includes: SS1, mixing the modified attapulgite, the mesoporous material, the clay, the binder and the second solvent to obtain a third mixture with a solid content of 10-50% by weight; SS2, mixing the third mixture, the molecular sieve and the large-particle alumina to obtain a second mixture with a solid content of 10-50% by weight, and controlling the pH value of the obtained second mixture to 2.5-4.5 before drying and calcining. The present disclosure does not impose specific restrictions on the mixing method, for example, it can be a stirring mixing method, and the stirring mixing time is also not specifically limited, for example, it can be 30-360 minutes.

[0055] In another specific embodiment of the present disclosure, step S2 includes: SS1, mixing the modified attapulgite, the mesoporous material, the clay, the binder and the second solvent to obtain a third mixture with a solid content of 10-50 weight %; SS2, mixing the molecular sieve, the large-particle alumina and the third solvent and controlling the pH value of the mixture to 2.5-4.5 to obtain a fourth mixture with a solid content of 10 to 50 weight %; mixing the fourth mixture with the third mixture, and drying and calcining the obtained second mixture.

[0056] The method disclosed in the present invention adopts a step-by-step mixing method to prepare a catalytic cracking catalyst with better catalytic activity. Using the catalyst in the catalytic cracking of crude oil is beneficial to further increase the total liquid yield and reduce the coke yield.

[0057] In a specific embodiment of the present disclosure, the drying conditions include: a temperature of 80-180°C; the calcining conditions include: a temperature of 400-600°C, a time of 0.5-5.0 hours; preferably, a temperature of 450-550°C, a time of 1.0-4.0 hours. In the present disclosure, drying can be performed by a method conventionally used by those skilled in the art, such as a spray drying method.

[0058] The third aspect of the present disclosure provides an application of the catalytic cracking catalyst with a multi-level pore structure provided by the first aspect of the present disclosure in catalytic cracking of crude oil. The method disclosed in the present disclosure has a higher total liquid yield and a lower coke yield.

[0059] In a specific embodiment of the present disclosure, the catalytic cracking conditions include: temperature of 450-560°C, time of 1-3s, catalyst-to-oil mass ratio of 3-10; preferably, temperature of 500-530°C, time of 1.5-3.0s, catalyst-to-oil mass ratio of 3-8.

[0060] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.

[0061] The raw materials used in the preparation of the catalyst are as follows: the solid content of kaolin is 76% by weight; the solid content of conventional pseudo-boehmite is 73.0% by weight, and the BET specific surface area is 341 m 2 / g, pore volume is 0.32mL / g, pore volume of 4-50nm accounts for 23% of the total pore volume. The solid content of the rare earth ultrastable Y zeolite REUSY used is 89.0% by weight, and the unit cell constant is In terms of weight percentage, the Na2O content is 0.77% and the RE2O3 content is 15.8%.

[0062] The specific preparation method of the large-particle pseudo-boehmite used in Examples 1-6 of the present disclosure is as follows: (1) At 40°C, a sodium aluminate solution with a concentration of 15gAl2O3 / L is reacted with a carbon dioxide gas with a volume fraction of 50% to form a gel, the carbon dioxide gas flow rate is 1L / min, and the endpoint pH value is controlled to be 10.5. (2) After the obtained slurry is transferred to a reactor, the temperature is first programmed to rise (heating rate of 5°C / min) to 75°C for aging for 60min, and then the temperature is programmed to rise (heating rate of 5°C / min) to 200°C for aging for 5h. (3) After the aging is completed, the obtained slurry is separated into solid and liquid, and washed continuously with 90°C deionized water for half an hour to obtain a product filter cake from which impurities are removed. (4) The filter cake is dried at 100°C for 3h to obtain a large-particle pseudo-boehmite with a solid content of 81.6% by weight, an average particle size of 9.6nm, and the number of particles with an average particle size of 5-30nm accounts for 88% of the total number of particles.

[0063] The solid content of mesoporous alumina is 92.0% by weight and the BET specific surface area is 344 m 2 / g, the total pore volume is 1.2mL / g, and the pore volume of 6-20nm accounts for 90% of the total pore volume.

[0064] The solid content of attapulgite is 79.8% by weight and the BET specific surface area is 98m 2 / g, the pore volume is 0.30mL / g, and the pore volume of 10-100nm accounts for 75% of the total pore volume.

[0065] The analysis and evaluation methods are described as follows:

[0066] Specific surface area and pore volume analysis: The ASAP 2405NV1.01 automatic adsorption instrument from Micromeritics, USA, was used, and the low temperature static nitrogen adsorption capacity method was used. The sample was heated to 1.33×10 -2 Pa, vacuum degassing at 300 ° C for 4 hours, using N2 as the adsorption medium, and measuring the adsorption-desorption isotherm of the sample at 77.4 K. The specific surface area of ​​the sample was calculated according to the BET formula, and the volume of N2 adsorbed by the sample when the relative pressure p / p0 = 0.98 was measured and converted into liquid nitrogen volume, i.e., the total pore volume. The micropore volume was calculated according to the t-plot method, and the pore volumes of 4-50nm, 10-100nm, 4-20nm, and 20-100nm pores were all calculated using the BJH desorption branch.

[0067] Catalyst strength: put a certain amount of catalyst into a fixed device and blow it for 5 hours under a constant airflow. Except for the first hour, the average wear percentage in the last four hours is called the catalyst wear index, and the unit is % per hour. The method and standard are: air lift method Q / SYLS0518-2002.

[0068] Measurement of sample particle size: The JEM-2000FX-II transmission electron microscope of Japan Electronics Company was used for analysis. The average particle size was obtained by randomly measuring more than 10 particle projections in the sample TEM image and taking the average value of the maximum circumscribed circle diameter.

[0069] Example 1

[0070] S1. 188 g of attapulgite and deionized water were mixed and stirred in a mass ratio of 1:6, and 36 wt % hydrochloric acid was added to adjust the pH value of the slurry to 2.0. The mixture was stirred at 60° C. for 30 min, filtered and dried at 100° C. to obtain modified attapulgite, which was recorded as AT-1 and had a pore size distribution as shown in FIG. Figure 2 shown.

[0071] According to analysis, the specific surface area of ​​modified attapulgite is 122m 2 / g, the total pore volume is 0.39mL / g, and the pore volume of 10-100nm accounts for 82% of the total pore volume.

[0072] S2, 163 grams of mesoporous alumina, 188 grams of modified attapulgite (AT-1) prepared in step S1, 105 grams of kaolin, 545 grams of aluminum sol and 753 grams of decationized water are added to a beating tank and beaten for 60 minutes to obtain a slurry with a solid content of 28%, 245 grams of large-particle pseudo-boehmite and 789 grams of REUSY molecular sieve slurry (including 337 grams of REUSY molecular sieve and a slurry solid content of 38 weight %) are added to the slurry, stirred for 90 minutes, 36 weight % hydrochloric acid is added to adjust the slurry pH to 3.5, the obtained mixed slurry has a solid content of 36 weight %, and then the obtained slurry is spray dried and formed, and calcined at 500 ° C for 1 hour to obtain the catalyst C1 provided by the present disclosure, whose composition and characteristic parameters are shown in Table 1, and the pore size distribution is as follows: Figure 1 As shown, the following embodiments are the same.

[0073] Example 2

[0074] S1. 125 g of attapulgite and deionized water were mixed and stirred evenly in a mass ratio of 1:10, 65 wt % nitric acid was added to adjust the pH value of the slurry to 3.0, the mixture was stirred at 80° C. for 60 min, and filtered to obtain a filter cake, which was recorded as modified attapulgite AT-2.

[0075] According to analysis, the specific surface area of ​​modified attapulgite is 138m 2 / g, the total pore volume is 0.44mL / g, and the pore volume of 10-100nm accounts for 90% of the total pore volume.

[0076] S2. Add 304 grams of mesoporous alumina, 125 grams of modified attapulgite (AT-2) prepared in step S1, 26 grams of kaolin, 909 grams of aluminum sol and 700 grams of decationized water into a slurrying tank and slurry for 120 minutes to obtain a slurry with a solid content of 29%. Add 123 grams of large-particle pseudo-boehmite and 789 grams of REUSY molecular sieve slurry (including 337 grams of REUSY molecular sieve and a slurry solid content of 38 weight %) to the slurry, continue stirring for 60 minutes, add nitric acid with a concentration of 65 weight % to adjust the slurry pH to 3.2, and the obtained mixed slurry has a solid content of 34 weight %. Then, the obtained slurry is spray-dried and formed, and calcined at 600°C for 1 hour to obtain the catalyst C2 provided in the present disclosure.

[0077] Example 3

[0078] S1. Mix 338 grams of attapulgite and deionized water in a mass ratio of 1:5 and stir evenly, add 36% by weight hydrochloric acid to adjust the pH value of the slurry to 2.0, stir at room temperature for 90 minutes, and filter; mix the filter cake with deionized water in a mass ratio of 1:5, adjust the pH value of the slurry to 3.5 with 5% by weight dilute hydrochloric acid, stir at 60°C for 90 minutes, and filter the filter cake obtained as modified attapulgite AT-3.

[0079] According to analysis, the specific surface area of ​​modified attapulgite is 122m 2 / g, the total pore volume is 0.40mL / g, and the pore volume of 10-100nm accounts for 86% of the total pore volume.

[0080] S2. Add 109 g of mesoporous alumina, 338 g of modified attapulgite (AT-3) prepared in step S1, 227 g of aluminum sol and 825 g of decationized water into a beating tank and beat for 90 min to obtain a slurry with a solid content of 28%. Add 343 g of large-particle pseudo-boehmite and 789 g of REUSY molecular sieve slurry (including 337 g of REUSY molecular sieve and a slurry solid content of 38 wt %) to the slurry, continue stirring for 90 min, add 36 wt % hydrochloric acid to adjust the slurry pH to 3.8, and the obtained mixed slurry has a solid content of 38 wt %. Then, the obtained slurry is spray-dried and formed, and calcined at 550° C. for 2 hours to obtain the catalyst C3 provided by the present invention.

[0081] Example 4

[0082] S1. Mix 251 g of attapulgite and deionized water in a mass ratio of 1:15 and stir evenly, add 36 wt% hydrochloric acid to adjust the pH value of the slurry to 3.5, stir at 40°C for 60 min, and filter; mix the filter cake with deionized water in a mass ratio of 1:15, adjust the pH value of the slurry to 3.0 with 20 wt% phosphoric acid, stir at 40°C for 60 min, filter, obtain the filter cake after filtering, and dry it at 150°C to obtain modified attapulgite, recorded as AT-4.

[0083] According to analysis, the specific surface area of ​​modified attapulgite is 116m 2 / g, the total pore volume is 0.39mL / g, and the pore volume of 10-100nm accounts for 80% of the total pore volume.

[0084] S2. Add 163 g of mesoporous alumina, 251 g of modified attapulgite (AT-4) prepared in step S1, 66 g of kaolin, 682 g of aluminum sol and 988 g of decationized water into a slurrying tank and slurry for 180 min. Add 36 wt% hydrochloric acid to adjust the pH of the slurry to 3.0 to obtain a slurry with a solid content of 26%. Add 184 g of large-particle pseudo-boehmite and 789 g of REUSY molecular sieve slurry (including 337 g of REUSY molecular sieve and a slurry solid content of 38 wt%) to the slurry. Continue stirring for 90 min. Add 36 wt% hydrochloric acid to adjust the pH of the slurry to 3.3. The solid content of the obtained mixed slurry is 32 wt%. The obtained slurry is then spray-dried and formed, and calcined at 450°C for 3 hours to obtain the catalyst C4 provided in the present disclosure.

[0085] Example 5

[0086] S1. 125 g of attapulgite and deionized water were mixed and stirred in a mass ratio of 1:12, 36 wt % hydrochloric acid was added to adjust the pH value of the slurry to 3.0, stirred at 90° C. for 30 min, filtered, and then dried at 120° C. to obtain modified attapulgite recorded as AT-5.

[0087] According to analysis, the specific surface area of ​​modified attapulgite is 122m 2 / g, the total pore volume is 0.40mL / g, and the pore volume of 10-100nm accounts for 88% of the total pore volume.

[0088] S2. Add 789 g of REUSY molecular sieve slurry (including 337 g of REUSY molecular sieve and 38 wt % solid content of the slurry), 147 g of large-grain pseudo-boehmite, 196 g of medium-porous alumina, 125 g of modified attapulgite (AT-5) prepared in step S1, 132 g of kaolin and 1413 g of decationized water into a slurrying tank and slurry for 180 min. Add 36 wt % hydrochloric acid to adjust the pH of the slurry to 3.2. Then add 455 g of aluminum sol and 333 g of silica sol. Continue stirring for 90 min. The obtained mixed slurry has a solid content of 28 wt %. Then, the obtained slurry is spray dried and formed, and calcined at 500° C. for 2 hours to obtain the catalyst C5 provided by the present invention.

[0089] Example 6

[0090] A catalytic cracking catalyst was prepared by the same method as in Example 1, except that in step S2, 54 g of medium-porous alumina, 75 g of modified attapulgite (AT-1) prepared in step S1, 553 g of kaolin, 545 g of aluminum sol and 711 g of decationized water were added to a slurrying tank and slurried for 60 min to obtain a slurry with a solid content of 34%, 61 g of large-particle pseudo-boehmite and 789 g of REUSY molecular sieve slurry (including 337 g of REUSY molecular sieve and a slurry solid content of 38 wt %) were added to the slurry, and the mixture was stirred for 90 min, and 36 wt % hydrochloric acid was added to adjust the pH of the slurry to 3.5. The solid content of the obtained mixed slurry was 36 wt %, and the obtained slurry was spray dried and formed, and calcined at 500° C. for 1 hour to obtain the catalyst C6 provided in the present disclosure.

[0091] Example 7

[0092] The catalytic cracking catalyst was prepared by the same method as in Example 1, except that the number of large-size pseudo-boehmite particles with an average particle size of 5-30 nm accounted for 80% of the total number of particles; the BET specific surface area of ​​the mesoporous alumina used was 200 m 2 / g, the total pore volume is 0.85mL / g, and the pore volume of 6-20nm accounts for 82% of the total pore volume.

[0093] The preparation method of large-particle pseudo-boehmite used in this embodiment is as follows: (1) At 45°C, a sodium aluminate solution with a concentration of 15gAl2O3 / L is reacted with a carbon dioxide gas with a volume fraction of 50% to form a gel, the carbon dioxide gas flow rate is 1L / min, and the end point pH value is controlled to be 10.5. (2) After the obtained slurry is transferred to a reactor, the temperature is first programmed to rise (heating rate of 5°C / min) to 60°C for aging for 60min, and then the temperature is programmed to rise (heating rate of 5°C / min) to 150°C for aging for 6h. (3) After aging, the obtained slurry is separated into solid and liquid, and washed continuously with 90°C deionized water for half an hour to obtain a product filter cake from which impurities are removed. (4) The filter cake is dried at 100°C for 3h to obtain a large-particle pseudo-boehmite with a solid content of 78.1% by weight, an average particle size of 8.5nm, and the number of particles with an average particle size of 5-30nm accounts for 82% of the total number of particles.

[0094] Comparative Example 1

[0095] The catalytic cracking catalyst was prepared by the same method as in Example 1, except that conventional pseudo-boehmite was used to replace the large-particle pseudo-boehmite, and no modified attapulgite or mesoporous alumina was contained. The conventional catalyst was prepared in this comparative example, and the preparation method was as follows:

[0096] 553 g of kaolin, 364 g of aluminum sol and 810 g of decationized water were added to a slurrying tank and slurried for 120 min. Then, 274 g of conventional pseudo-boehmite and 789 g of REUSY molecular sieve slurry (including 337 g of REUSY molecular sieve and 38 wt % solid content of slurry) were added, stirred for 60 min, and 36 wt % hydrochloric acid was added to adjust the slurry pH to 3.5. The solid content of the obtained mixed slurry was 36 wt %. The obtained slurry was then spray dried and formed, and calcined at 500 ° C for 1 hour to obtain the comparative catalyst DC1, whose pore size distribution is as shown in Figure 3 shown.

[0097] Comparative Example 2

[0098] The catalytic cracking catalyst was prepared by the same method as in Example 1, except that the catalyst of this comparative example did not contain modified attapulgite. Step S2 was as follows:

[0099] 163 grams of medium-porous alumina, 303 grams of kaolin, 545 grams of aluminum sol and 744 grams of decationized water were added to a slurrying tank and slurried for 60 minutes to obtain a slurry with a solid content of 28%. 245 grams of large-particle pseudo-boehmite and 789 grams of REUSY molecular sieve slurry (including 337 grams of REUSY molecular sieve and a slurry solid content of 38 weight%) were added to the slurry, stirred for 90 minutes, and 36 weight% hydrochloric acid was added to adjust the slurry pH to 3.5. The solid content of the obtained mixed slurry was 36 weight%. The obtained slurry was then spray-dried and formed, and calcined at 500°C for 1 hour to obtain a comparative catalyst DC2.

[0100] Comparative Example 3

[0101] The catalytic cracking catalyst was prepared by the same method as in Example 1, except that the comparative example did not use mesoporous alumina. Step S2 was as follows:

[0102] 188 g of modified attapulgite (AT-1), 303 g of kaolin and 719 g of decationized water were added to a slurrying tank and slurried for 60 min to obtain a slurry with a solid content of 31%. 245 g of large-particle pseudo-boehmite, 545 g of aluminum sol and 789 g of REUSY molecular sieve slurry (including 337 g of REUSY molecular sieve and a slurry solid content of 38 wt%) were added to the slurry, stirred for 90 min, and 36 wt% hydrochloric acid was added to adjust the slurry pH to 3.5. The solid content of the obtained mixed slurry was 36 wt%. The obtained slurry was then spray dried and formed, and calcined at 500°C for 1 hour to obtain a comparative catalyst DC3.

[0103] Comparative Example 4

[0104] The catalytic cracking catalyst was prepared by the same method as in Example 1, except that conventional pseudo-boehmite was used instead of large-diameter pseudo-boehmite in this comparative example. Step S2 was as follows:

[0105] 163 g of mesoporous alumina, 188 g of modified attapulgite (AT-1), 105 g of kaolin, 545 g of aluminum sol and 724 g of decationized water were added to a slurrying tank and slurried for 60 min to obtain a slurry with a solid content of 29%. 274 g of conventional pseudo-boehmite and 789 g of REUSY molecular sieve slurry (including 337 g of REUSY molecular sieve and a slurry solid content of 38 wt%) were added to the slurry, stirred for 90 min, and 36 wt% hydrochloric acid was added to adjust the slurry pH to 3.5. The obtained mixed slurry had a solid content of 36 wt%. The obtained slurry was then spray dried and formed, and calcined at 500°C for 1 hour to obtain a comparative catalyst DC4.

[0106] Comparative Example 5

[0107] The catalytic cracking catalyst was prepared by the same method as in Example 1, except that the catalyst of this comparative example did not contain modified attapulgite. Step S2 was as follows:

[0108] 351 grams of medium-porous alumina, 105 grams of kaolin, 545 grams of aluminum sol and 753 grams of decationized water were added to a slurrying tank and slurried for 60 minutes to obtain a slurry with a solid content of 28%. 245 grams of large-particle pseudo-boehmite and 789 grams of REUSY molecular sieve slurry (including 337 grams of REUSY molecular sieve and a slurry solid content of 38 weight%) were added to the slurry, stirred for 90 minutes, and 36 weight% hydrochloric acid was added to adjust the slurry pH to 3.5. The solid content of the obtained mixed slurry was 35 weight%. The obtained slurry was then spray-dried and formed, and calcined at 500°C for 1 hour to obtain a comparative catalyst DC5.

[0109] Table 1 Composition and physicochemical properties of catalysts

[0110]

[0111] Catalysts C1-C7 prepared in Examples 1-7 and catalysts DC1-DC5 prepared in Comparative Examples 1-5 were pre-aged at 800°C and 100% steam for 17 hours and then evaluated on a small fixed fluidized bed (ACE) device. The properties of the reaction raw oil are shown in Table 2, the catalyst-oil weight ratio is 8.0, the sample loading is 9g, the reaction temperature is 520°C, and the evaluation results are listed in Table 3.

[0112] Conversion rate = gasoline yield + liquefied gas yield + dry gas yield + coke yield;

[0113] Coke selectivity = coke yield / conversion rate × 100;

[0114] Gasoline selectivity = gasoline yield / conversion rate × 100;

[0115] Light olefin selectivity = (propylene yield + butene yield) / conversion rate × 100;

[0116] Total liquid yield = liquefied gas yield + gasoline yield + diesel yield.

[0117] Table 2 Raw oil properties

[0118]

[0119] Table 3 Evaluation results

[0120]

[0121]

[0122]

[0123] As shown in Table 1 and the accompanying drawings, compared with Comparative Examples 1 to 5, the total pore volume of the catalysts prepared in Examples 1 to 7 and the proportion of 4-6nm, 6-20nm, and 20-100nm pores are significantly increased. The results in Table 3 show that the heavy oil yield is low, the coke selectivity is improved, and the selectivity of light olefins (propylene and butene) and gasoline is high. It can be seen that the catalytic cracking catalyst prepared by the present invention has a rich multi-stage medium and macroporous structure, and is used for excellent heavy oil cracking ability and good product selectivity in the catalytic cracking process of heavy crude oil.

[0124] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0125] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0126] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A catalytic cracking catalyst having a multi-level pore structure, which comprises, based on the total weight of the catalytic cracking catalyst, 5-30 wt% of large-particle alumina, 5-40 wt% of mesoporous material, 5-35 wt% of modified attapulgite, 20-50 wt% of molecular sieve, 2-35 wt% of binder and 0-20 wt% of clay; the number of particles with an average particle size of 5-30 nm in the large-particle alumina accounts for more than 80% of the total number of particles; the mesoporous material contains silicon and / or aluminum; The total pore volume of the catalytic cracking catalyst is above 0.25 mL / g, the pore volume of 4-6 nm pores accounts for 10-35% of the total pore volume, the pore volume of 6-20 nm pores accounts for 30-60% of the total pore volume, and the pore volume of 20-100 nm pores accounts for 10-30% of the total pore volume.

2. The catalytic cracking catalyst according to claim 1, wherein The catalytic cracking catalyst contains 10-30 weight percent of large-particle alumina, 10-35 weight percent of mesoporous material, 10-35 weight percent of modified attapulgite, 25-45 weight percent of molecular sieve, 5-30 weight percent of binder and 0-15 weight percent of clay.

3. The catalytic cracking catalyst according to claim 1, wherein The total pore volume of the catalytic cracking catalyst is 0.3-0.5 mL / g, the pore volume of the 4-6 nm pores accounts for 15-35% of the total pore volume, the pore volume of the 6-20 nm pores accounts for 30-55% of the total pore volume, and the pore volume of the 20-100 nm pores accounts for 15-30% of the total pore volume.

4. The catalytic cracking catalyst according to claim 1, wherein The number of particles with an average particle size of 5-30 nm in the large-particle alumina accounts for 85-95% of the total number of particles; the large-particle alumina is selected from one or more of large-particle pseudo-boehmite, large-particle boehmite and large-particle aluminum sol, preferably large-particle pseudo-boehmite; The total pore volume of the mesoporous material is 0.8-2.5 mL / g, preferably 1.0-2.2 mL / g, the pore volume of 6-20 nm pores accounts for more than 80% of the total pore volume, preferably 85-95%, and the specific surface area is 200-400 m 2 / g, preferably 220-400m 2 / g; the mesoporous material is selected from one or more of conventional pseudo-boehmite, alumina, silica and alumina-silica, preferably conventional pseudo-boehmite and / or alumina; The total pore volume of the modified attapulgite is 0.3 mL / g or more, preferably 0.3-0.5 mL / g, the pore volume of 10-100 nm pores accounts for more than 80% of the total pore volume, preferably 85-95%, and the specific surface area is 100 m 2 / g or more, preferably 100-300m 2 / g; The molecular sieve is selected from NaY type molecular sieve, and the NaY type molecular sieve is one or more of the modified high silicon-aluminum ratio Y zeolite, MFI type zeolite and Beta zeolite; The binder is selected from one or more of aluminum sol, silica sol, silica-alumina sol, acidified pseudo-boehmite, aluminum phosphate sol and zirconium sol, preferably aluminum sol and / or silica sol; The clay is selected from one or more of kaolin, bentonite, montmorillonite, sepiolite, diatomaceous earth and rectorite, preferably kaolin.

5. A method for preparing the catalytic cracking catalyst having a multi-level pore structure according to any one of claims 1 to 4, the method comprising: S1, mixing attapulgite and a first solvent, controlling the pH value of the obtained first mixture to be 1.5-4.5, stirring at 20-90° C. for 30-120 min, and taking out a solid to obtain modified attapulgite; S2, mixing the modified attapulgite, mesoporous material, clay, molecular sieve, large-size alumina, binder and a second solvent, controlling the pH value of the obtained second mixture to be 2.5-4.5, and then drying and calcining.

6. The method according to claim 5, wherein: Step S1 comprises: mixing the attapulgite and the first solvent in a weight ratio of 1:(5-20), and adjusting the pH value of the first mixture to 1.5-4.0 using an acid solution; The acid solution contains organic acid and / or inorganic acid; the organic acid is selected from one or more of oxalic acid, acetic acid and citric acid, and the inorganic acid is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, ammonium sulfate and ammonium chloride.

7. The method according to claim 5, wherein: Step S2 includes: SS1, mixing the modified attapulgite, the mesoporous material, the clay, the binder and the second solvent to obtain a third mixture with a solid content of 10-50 wt %; SS2, mixing the third mixture, the molecular sieve and the large-particle alumina to obtain a second mixture with a solid content of 10-50 wt %, controlling the pH value of the obtained second mixture to be 2.5-4.5, and then drying and calcining; or, SS2. Mix the molecular sieve, the large-particle alumina and the third solvent and control the pH value of the mixture to be 2.5-4.5 to obtain a fourth mixture with a solid content of 10-50 weight %; mix the fourth mixture with the third mixture, and dry and calcine the obtained second mixture.

8. The method according to claim 7, wherein: The drying conditions include: a temperature of 80-180° C.; the calcining conditions include: a temperature of 400-600° C. and a time of 0.5-5.0 hours.

9. Use of the catalytic cracking catalyst with a multi-level pore structure according to any one of claims 1 to 4 in catalytic cracking of crude oil.

10. The use according to claim 9, wherein: The catalytic cracking conditions include: temperature of 450-560° C., time of 1-3 s, and catalyst-oil mass ratio of 3-10.